Airflow Characteristic of UAV Quadcopter Propeller Blade Using Computational Fluid Dynamics (CFD) - Azizan, Najma Nazlifah; Sapit, Azwan (Progress in Aerospace and Aviation Technology, 2022)
In this study, the main focus is to study of air flow characteristic of UAV quadcopter propeller at incorporate blade profile using variable angle of attack (AoA) and revolution per minute (RPM) with its twisted blade using Computational Fluid Dynamics (CFD) / Ansys tool. Three propellers have been designed which Propeller 1 is untwisted while Propeller 2 and 3 twisted at certain angle. Three speeds which are 4000 rpm, 6000 rpm and 8000 rpm have been set for each propeller are being analysed using ANSYS Fluid Flow (fluent). The result shows the different thrust force generated by three propellers and Propeller 2 (33.6757 N) has the highest thrust force generated compared to Propeller 1 and 3 especially at 8000 rpm. This is due to the suitable twisting angle profile that has been set at the Propeller 2 at this operating speed. For comparison, Propeller 3 produce the highest thrust force of 18.44 N at 6000 rpm exceeding Propeller 2 which is 17.81 N. To summarize, each propeller blade profile has a distinctive aerodynamic performance and should be adopted by matching the flight operating condition. Higher rpm generate higher thrust force, and increase lift and drag coefficient.